Sources of political parties’ campaign expenditure in Nigeria’s Fourth Republic: examining the 2015 general election - Sule, Babayo; Mat, Bakri; Mohd Sani, Mohd Azizuddin; Ibrahim, Saalah Yakubu (SAGE Publications, 2019)
A periodic election is a fundamental pillar and backbone of any democratic regime, and for a proper election to take place there must be some activities, most especially by parties and contestants to vote for them most especially competing to secure the electorates. These activities require huge expenditure from the parties and their financiers through campaigns, media advertisements and other related activities. The problem is that parties and their candidates are allowed, in Nigeria constitutionally and by the Electoral Act 2010, to source their campaign finance privately, which has led to illegal financing. The objective of this paper is to examine the sources of parties’ campaign expenditure in the Fourth Republic, taking the 2015 General Election as the case study. The research used a qualitative method of data collection and analysis where both primary and secondary sources were used. The primary source was an in-depth personal interview with some selected informants/participants from the categories of stakeholders in the electoral process, parties, and agencies responsible for regulating their activities. The secondary source was the use of available documents such as books, journals and Internet sources on the subject matter of the study. The data obtained were analysed and interpreted using thematic analytical interpretations from the informants’ views and the existing data in the field. The research discovered that there are basically six major sources of campaign expenditure for parties and that some of the sources are illegal and the spending has violated the regulations. The research recommends thorough supervision and monitoring of the sources of parties’ campaign expenditure and the spending process.